(untitled) (Ustozlar uchun, 2026)
: This article explores effective strategies for teaching reading in academic contexts. It addresses the challenges faced by learners and presents instructional techniques that enhance comprehension and critical thinking. The significance of integrating reading skills into academic curricula is emphasized, alongside practical applications for educators.